Self-Specific Stimuli Interact Differently than Non-Self-Specific Stimuli with Eyes-Open Versus Eyes-Closed Spontaneous Activity in Auditory Cortex - Qin, Pengmin; Grimm, Simone; Duncan, Niall W.; Holland, Giles; Guo, Jia shen; Fan, Yan; Weigand, Anne; Baudewig, Juergen; Bajbouj, Malek; Northoff, Georg (Frontiers in Human Neuroscience, 2013)
Previous studies suggest that there may be a distinct relationship between spontaneous neural activity and subsequent or concurrent self-specific stimulus-induced activity. This study aims to test the impact of spontaneous activity as recorded in an eyes-open (EO) resting state as opposed to eyes-closed (EC) on self-specific versus non-self-specific auditory stimulus-induced activity in fMRI. In our first experiment we used self-specific stimuli comprised of the subject's own name and non-self-specific stimuli comprised of a friend's name and an unknown name, presented during EO versus EC baselines in a 3 name condition × 2 baseline design. In Experiment 2 we directly measured spontaneous activity in the absence of stimuli during EO versus EC to confirm a modulatory effect of the two baseline conditions in the regions found to show an interaction effect in Experiment 1. Spontaneous activity during EO was significantly higher than during EC in bilateral auditory cortex and non-self-specific names yielded stronger signal changes relative to EO baseline than to EC. In contrast, there was no difference in response to self-specific names relative to EO baseline than to EC despite the difference between spontaneous activity levels. These results support an impact of spontaneous activity on stimulus-induced activity, moreover an impact that depends on the high-level stimulus characteristic of self-specificity.